Object-Oriented Ontology: A New Theory of Everything: Graham Harman: Object-Oriented Ontology: A New Theory of Everything. St. Ives: Penguin Books, 2018, 295 pp. - Jiménez Morales, Luis Alberto (Analysis. Journal of Philosophical Research, 2020)
Book Review: Graham Harman (2018). Object-Oriented Ontology: A New Theory of Everything. Great Britain: Penguin Books. 295 pages. The Object-Oriented Ontology is a relatively new current within the contemporary problems of philosophy. One of its main exponents is the American philosopher Graham Harman. To understand Harman’s philosophy, it is necessary to determine what is the fundamental problem that concerns him. His proposal is articulated as a critical dialogue with the natural sciences and with the implications of modern and contemporary philosophy. The aim of this review is one of his most recent works: Object-Oriented Ontology: A New Theory of Everything, which appeared in Penguin Books in 2018